(untitled) (Global Journal of Human-Social Science, 2020)
This article examines the evolution of propaganda since the ancient times until the present time, as well as the ancient proto-propaganda. The authors analyze the transitioning processes from the ancient times to early Christianity from the perspective of state ideology. The article also studies the emergence of Protestantism and its role in the development of Capitalism and establishment of the 20 th century economic system, which the authors call the Keynes-Bernays economic model. The newest propagandistic opportunities and the potential for processing big data is also reviewed. The article explores the phenomenon of the recent decade -social networks as a new instrument of propaganda. In this work, the authors used the systemic approach as well as the psychological method and the method of comparative historical analysis, using modern terminology including the terms newly introduced by the authors, which made it possible to improve the methodological foundation of the study.